1996
DOI: 10.1002/(sici)1520-6661(199611/12)5:6<333::aid-mfm8>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in early adolescence: Are there obstetric risks?

Abstract: The purpose of this study was to determine if early adolescence imparts a significant obstetric risk in young primiparas relative to adult primiparas. The records of 239 young primiparas (<16 years) and 148 older primiparas (18–29 years) were reviewed for demographic information, antepartum complications, mode of delivery, length of labor, episiotomy, lacerations, birthweight, and length of gestation. The young adolescents were shorter, had an earlier age at menarche, a lower pregravid body mass index, and a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…Jacobsson et al showed in their studies that prenatal mortality, intrauterine fetal death, and neonatal death increased with age [19]. Pregnancies at both extremes of reproductive age represent many complications during pregnancy and birth which result in increased maternal and newborn morbidity and mortality [22]. The high rates of an ovulation during adolescence and after the age of 35 may be interpreted as an adaptation to high risk pregnancies during these phases of life.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Jacobsson et al showed in their studies that prenatal mortality, intrauterine fetal death, and neonatal death increased with age [19]. Pregnancies at both extremes of reproductive age represent many complications during pregnancy and birth which result in increased maternal and newborn morbidity and mortality [22]. The high rates of an ovulation during adolescence and after the age of 35 may be interpreted as an adaptation to high risk pregnancies during these phases of life.…”
Section: Introductionsupporting
confidence: 72%
“…In older literature (e.g. Moerman 1982) [30], the increased risk of cesarean section among teenage mothers was mentioned, however according to more recent papers no increased rate of cesarean sections is found among very young adolescent mothers [22,23,31]. The results of the present paper support these findings, as the teenage mothers of the present sample had the lowest rate of cesarean sections of the whole sample.…”
Section: Discussionmentioning
confidence: 92%
“…There is a higher probability that the adolescent mothers are exposed to negative pregnancy outcomes and mortality related to maternity compared to adult mothers (4). The incidence of adolescent pregnancies in the world varies between 3.2% and 42% (6,8). In the literature, the adolescent pregnancy ratios were reported to be 0.9-21% in European countries, 10.6% in USA, 0.4-4.2% in Asia and 8-50% in Africa (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…While a lower risk of cesarean delivery in adolescents has been previously described by other studies in diverse settings, [15][16][17][18][19][20] these studies analyzed maternal age as a binary variable, with each study using inconsistent cutoff values to distinguish between adolescent and adult groups. As a result, these studies were unable to depict a robust association between maternal age and mode of delivery.…”
Section: Commentsmentioning
confidence: 99%
“…14 However, these risk factors notwithstanding, several studies have shown that adolescents actually have lower rates of cesarean compared with their adult counterparts. [15][16][17][18][19][20] Such mixed and often contradictory findings may arise from several inconsistencies in the methodology of these studies, including a tendency to analyze only a few influential factors in isolation, the use of arbitrary age group clusters instead of analyzing the entire spectrum of adolescent age, and discounting the potential influence of the adolescent's race/ethnicity. Given these shortcomings in the existing literature, we sought to systematically evaluate the complex interplay between maternal age, race/ethnicity, and primary cesarean delivery among young women delivering in the United States.…”
mentioning
confidence: 99%